PENDAMPINGAN IBU HAMIL MELALUI PROGRAM ONE STUDENT ONE CLIENT (OSOC) DI WILAYAH KERJA PUSKESMAS SIDOHARJO KABUPATEN SRAGEN - Fauziah, Ani Nur (P3M STIKES Aisyiyah Surakarta, 2018)
Maternal Mortality Ratein the Central Java in 2012-2014 has significantly increased in 2012: 675 of cases, 2013: 668 of cases, 2014: 711 of cases, while in 2015 and 2016 decreased: 2015: 619 of cases and 2016: 602 of cases. One Student One Client Program (OSOC) is a program launched by the Governmentof Central Java Provinceas an effort to decrease The Rate of Maternal Mortality in Central Java.The targets and outcomes of this activity are scientific publications and? journals continuously also midwifery care process to the mother; pregnant, childbirth, childbirth, birth control and newborn care.The cooperation between healths professional in midwifery process later can contribute in decreasing Maternal Mortality Rate.The method used is direct learning experience in the community. Each learner will get one client (pregnant mother) through a midwife coordinator in Work Area of Puskesmas Sidoharjo to achieve one student one client.The techniques of data collection are forms of; pregnancy midwifery care , delivery, puerper, new baby born and KB. This accompaniment was carried out for 5 months from April - August 2017 in the working area of Puskesmas of Sidoharjo.The result of this are the majority of pregnant mothers can be through pregnancy with healthy and the increase of awareness and knowledge of pregnant women.?